INFLUENCE OF PROBIOTIC CULTURE LACTOBACILLUS RHAMNOSUS GG (LGG) ON IMMUNE RESPONSE OF ORGANISM - A.V. Surzhik ("Paediatrician" Publishers LLC, 2009)
This article presents review of data of influence of probiotic culture Lactobacillus rhamnosus GG on intestinal biocenosis. Main attention was given to influence of L. rhamnosus GG on functions of immune system. Key words: probiotics, Lactobacillus rhamnosus GG, immune response. (Voprosy sovremennoi pediatrii - Current Pediatrics. 2009;8(2):54-58)